Hubungan Pengetahuan Sikap Ibu dan Dukungan Suami dengan Pemilihan Alat Kontrasepsi Implan - Eva Safitriana; Hasbiah Hasbiah; Rizki Amalia (Universitas Batanghari Jambi, 2022)
Implant contraceptives are contraceptives that have the same long-term effectiveness as the IUD or spiral. It can be seen that implants are a more effective contraceptive and are easier to install. This study aims to determine the relationship between knowledge, attitudes and husband's support simultaneously with the selection of implant contraceptives at the Belida Darat Health Center, District. Muara Enim 2021. The design of this research is an Analytical Survey using a cross sectional research design. The population in this study were all new family planning acceptors and active family planning in 2021, as many as 38 respondents and a total sample of 38 respondents. The sampling technique used is Accidental Sampling. Data analysis used chi square. The results of this study from 38 respondents, knowledge p value = 0.003, attitude p-value = 0.02 and husband's support p-value = 0.01. Midwives are expected to improve counseling methods for family planning acceptors, especially in the selection of contraceptive implants.